2007
DOI: 10.1083/jcb.200704015
|View full text |Cite
|
Sign up to set email alerts
|

Cells migrating to sites of tissue damage in response to the danger signal HMGB1 require NF-κB activation

Abstract: Tissue damage is usually followed by healing, as both differentiated and stem cells migrate to replace dead or damaged cells. Mesoangioblasts (vessel-associated stem cells that can repair muscles) and fibroblasts migrate toward soluble factors released by damaged tissue. Two such factors are high mobility group box 1 (HMGB1), a nuclear protein that is released by cells undergoing unscheduled death (necrosis) but not by apoptotic cells, and stromal derived factor (SDF)–1/CXCL12. We find that HMGB1 activates the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
96
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 235 publications
(102 citation statements)
references
References 28 publications
(44 reference statements)
4
96
0
2
Order By: Relevance
“…A number of studies have indicated that HMGB1 acts as a potential host cell-derived, chemotactic factor to promote migration of several cell types (Degryse and de Virgilio, 2003). These cells include neurites (Fages et al, 2000), smooth muscle cells (Degryse et al, 2001), myoblast cells (Fages et al, 2000), tumor cells (Fages et al, 2000; Huttunen et al, 2002; Palumbo and Bianchi, 2004; Palumbo et al, 2004), hepatic stellate cells (Wang et al, 2013b), stem cells (Palumbo et al, 2009; Palumbo et al, 2007; Palumbo et al, 2004), endothelial cells (Furlani et al, 2012), keratinocytes (Ranzato et al, 2009), monocytes (Pedrazzi et al, 2007; Rouhiainen et al, 2004), dendritic cells (Dumitriu et al, 2007; Yang et al, 2007), and neutrophils (Orlova et al, 2007; Palumbo et al, 2009; van Zoelen et al, 2009). The potential mechanisms include HMGB1-mediated signaling transduction (e.g., ERK (Degryse et al, 2001; Ranzato et al, 2009), Cdc42 (Fages et al, 2000), Rac (Fages et al, 2000), JNK (Wang et al, 2013b), PI3K/AKT (Wang et al, 2013b) and Src (Palumbo et al, 2009)), transcriptional factor activation (NF-κB), and chemokine production.…”
Section: Hmgb1 Functionmentioning
confidence: 99%
“…A number of studies have indicated that HMGB1 acts as a potential host cell-derived, chemotactic factor to promote migration of several cell types (Degryse and de Virgilio, 2003). These cells include neurites (Fages et al, 2000), smooth muscle cells (Degryse et al, 2001), myoblast cells (Fages et al, 2000), tumor cells (Fages et al, 2000; Huttunen et al, 2002; Palumbo and Bianchi, 2004; Palumbo et al, 2004), hepatic stellate cells (Wang et al, 2013b), stem cells (Palumbo et al, 2009; Palumbo et al, 2007; Palumbo et al, 2004), endothelial cells (Furlani et al, 2012), keratinocytes (Ranzato et al, 2009), monocytes (Pedrazzi et al, 2007; Rouhiainen et al, 2004), dendritic cells (Dumitriu et al, 2007; Yang et al, 2007), and neutrophils (Orlova et al, 2007; Palumbo et al, 2009; van Zoelen et al, 2009). The potential mechanisms include HMGB1-mediated signaling transduction (e.g., ERK (Degryse et al, 2001; Ranzato et al, 2009), Cdc42 (Fages et al, 2000), Rac (Fages et al, 2000), JNK (Wang et al, 2013b), PI3K/AKT (Wang et al, 2013b) and Src (Palumbo et al, 2009)), transcriptional factor activation (NF-κB), and chemokine production.…”
Section: Hmgb1 Functionmentioning
confidence: 99%
“…These results suggested that RAGE signaling plays an important role in microglia migration and that factors in the culture medium might stimulate basal microglia migration in a RAGE-mediated manner. One candidate RAGE agonist with the ability to stimulate basal microglia transmigration is high mobility group protein 1 (HMGB1), an established RAGE ligand (51-53) released by activated macrophages (54) and implicated in RAGE-dependent migration of several cell types (55)(56)(57)(58). Indeed, the microglia culture medium contained HMGB1 (Fig.…”
Section: S100b Stimulates Microglia Transmigration In a Rage-dependentmentioning
confidence: 99%
“…In addition, activation of NF-B and ERK1/2 is required for initiation of pro-inflammatory responses (Marui et al 1993;Lockyer et al 1998;Rose et al 2010). HMGB1 is known to activate NF-B and ERK1/2 in vascular inflammatory responses (Park et al 2006;Palumbo et al 2007;Yang and Tracey 2010). Therefore, we evaluated the effects of VCN and SCL on the activation of NF-B and ERK1/2 by HMGB1.…”
Section: Effects Of Vcn and Scl On Hmgb1-stimulated Production Of Tnfmentioning
confidence: 98%